S27 Have recent changes to health policies increased diagnostic delay amongst migrant patients with active tb?. (15th November 2017) - Potter, JL; Burman, M; Tweed, C; Vanghuela, D; White, VLC; Swinglehurst, D; Griffiths, CJ; Kunst, H
Abstract : Background: In April 2014 the UK government launched the 'Migrant and Visitor Cost Recovery Programme' (MVCRP): a series of policy changes to recoup costs from 'chargeable' (largely non-UK born) patients. In England approximately 75% of tuberculosis (TB) cases occur in those born abroad. Delays in treatment increase the risk of morbidity and mortality and threaten public health. We considered whether time between symptom onset and starting treatment for TB has increased since the introduction of the MVCRP. Methods: Adult TB cases notified on the London TB Register across Barts Health NHS Trust between 2011 and 2016 were identified. Incomplete data sets were excluded. We examined time to treatment between UK born and Non-UK born patients before and after the policy change using a student paired t-test. To further evaluate non-UK born patients, we labelled a delayed diagnosis as ≥median time to treatment for all patients (79 days). We used a chi-squared test to look for an association before developing a logistic regression model adjusting for age, sex, occupation, time in the UK and social risk factors. Other potential confounders were not included in the final model if they had no effect on the original association. Analyses were performed using Stata15. Results: 2237 cases were identified (for summary statistics see Table 1 ). Pre-MVCRP there was no difference in the mean time to treatment between the UK born and non-UK born (p=0.559) but post MVCRP there was a non-significant increase for the non-UK born (p=0.076). Amongst non-UK born patients only, time to treatment increased following introduction of MVCRP (p=0.0008) and they were more likely to have a delayed diagnosis (p<0.001). A logistic regression model adjusting for confounders found that the non-UK born were 37% more likely to have a delay in diagnosis post introduction of the MVCRP (aOR 1.37, 95% CI 1.13–1.66, p=0.001). Conclusion: Our findings suggest an association between the introduction of the MVCRP and risk of a delayed TB diagnosis amongst migrants. We cannot exclude the possibility of unknown confounders. However, further investigation into the effect of policies restricting access to healthcare for migrants is urgently needed.